If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b in (-oo:+oo)
3*b-((3*b)/2)-4 = 0
3*b+(-3/2)*b-4 = 0
3/2*b-4 = 0 // + 4
3/2*b = 4 // : 3/2
b = 4/3/2
b = 8/3
b = 8/3
| 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c | | Ax(x-1)+B(x+1)(x-1)+C(x+1)x=x^2+4 | | -4b=11 | | 8x+2=4x-24 | | 11-6= | | -34=-2(3x+5) | | 6f+5(4f+3)= | | 6(2n+8)=102 | | 107=107(47-y) | | 4(3n-3)=48 | | 2x^2+25x+20=-x^2-8 | | 2(y-1)=3(y-6) | | 2x(x+3)=2x^2+6x |